2010
DOI: 10.2353/ajpath.2010.090539
|View full text |Cite
|
Sign up to set email alerts
|

Podocalyxin EBP50 Ezrin Molecular Complex Enhances the Metastatic Potential of Renal Cell Carcinoma Through Recruiting Rac1 Guanine Nucleotide Exchange Factor ARHGEF7

Abstract: Podocalyxin was initially identified in glomerular podocytes to critically maintain the structural and functional integrity of the glomerular ultrafiltrative apparatus. Lately, it has emerged as a malignant marker in tumors arising from a variety of tissue origins. By immunohistochemistry, we identified that 9.6% of renal cell carcinoma patients overexpress this protein. This subset of patients had significantly shorter disease-specific and overall survivals, and, importantly, we established podocalyxin overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 33 publications
(38 reference statements)
5
103
0
Order By: Relevance
“…We recently demonstrated that EBP50 interacts with b-PIX through its first PDZ domain, and b-PIX associates with the podocalyxin-EBP50-ezrin complex. 19 The interaction between EBP50 and b-PIX was confirmed by co-immunoprecipitation (Figure 5a). Both basal and MRC-5 conditioned medium-dependent Rac1 activation decreased upon b-PIX knockdown, confirming the involvement of b-PIX in the Rac1 activation, using MRC-5 conditioned medium (Figure 5b).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…We recently demonstrated that EBP50 interacts with b-PIX through its first PDZ domain, and b-PIX associates with the podocalyxin-EBP50-ezrin complex. 19 The interaction between EBP50 and b-PIX was confirmed by co-immunoprecipitation (Figure 5a). Both basal and MRC-5 conditioned medium-dependent Rac1 activation decreased upon b-PIX knockdown, confirming the involvement of b-PIX in the Rac1 activation, using MRC-5 conditioned medium (Figure 5b).…”
Section: Resultsmentioning
confidence: 81%
“…18 Previously, we identified a novel interaction between EBP50 and b-PIX, a specific GEF for Rac1 and Cdc42, and proposed that the podocalyxin-EBP50-ezrin complex recruited b-PIX and, thereby, enhanced the metastatic potential of renal cell carcinoma. 19 To confirm the role of EBP50 in Rac1 activation in living cells, we measured Rac1 activity in EBP50 knockdown MDCK cells in the presence of MRC-5 conditioned medium, which induces Rac1 activation via bioactive hepatocyte growth factor (HGF). 28 EBP50 knockdown not only resulted in diminished basal Rac1 activity but also significantly reduced the level of Rac1 activation compared with mock cells exposed to MRC-5 conditioned medium (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computerassisted quantitative analysis (Image Pro Plus 6.0, MediaCybernetics, SilverSpring, MD, USA) was performed as previously described. 22 Briefly, 5 glomeruli and 20 randomly selected nonoverlapping high-power fields of each renal cortical section were captured by a PROVIS AX80 microscope (Olympus, Tokyo, Japan) equipped with a 12-bit RETIGA 1300 digital camera (QImaging, Burnaby, Canada). The captured images were then analyzed by Image Pro Plus software.…”
Section: Immunohistochemistrymentioning
confidence: 99%